Economic Behavior in Political Context - Bartels, Larry M; Brady, Henry E (American Economic Review, 2003)
Inviting political scientists to tell economists how they could do better work is an act of disciplinary generosity. The reality is that contemporary political science is a net importer of ideas and methods from other disciplines, and from none more than economics. Indeed, some of the most exciting research in political science in the past 40 years has involved the incorporation of ideas from economics. We have neither the space nor the mandate to summarize that research here, but refer interested readers to Gary J. Miller's (1997) extensive review. Our aim here is to offertwo modest case studies of specific instances of overlap between the interests and research efforts of economists and political scientists. Our first case study focuses on describing and explaining participation in the workforce, the polity, and many other social activities and organizations. Our second case study focuses on the impact of political processes and institutions on macroeconomic policies and performance. In both these instances the work of economists has been quite fruitful—but also, we think, hampered by a characteristic overreliance on standard economic models and methods. However, in both areas, recent developments may point the way toward a more constructive research style combining the theoretical and empirical rigor of economics with a broader and more eclectic approach familiar to political scientists.